2015
DOI: 10.1093/jee/tov075
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Potential of Clove Essential Oil and Its Constituents on Cacopsylla chinensis (Hemiptera: Psyllidae) in Laboratory and Field

Abstract: Cacopsylla chinensis (Yang and Li) (Hemiptera: Psyllidae) is an important pest of pear in China. As an alternative to conventional chemical pesticides, botanicals including essential oils and their constituents could provide an eco-friendly and nonhazardous control method. In this study, the essential oil of clove buds (Syzygium aromaticum) was obtained by hydrodistillation. Five constituents, accounting for 99.89% of the oil, were identified by gas chromatography-mass spectrometry, and the major constituents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 29 publications
3
29
0
2
Order By: Relevance
“…In this study, the three major compounds of CO were found to be eugenol (61%), β‐caryophyllene (17.9%), and eugenol acetate (11.73%) by GC‐MS (Table ). This is in accordance with previous results published by Prashar and others () and Tian and others (). According to Chaieb and others (), the major components of CO are eugenol (88.58%), eugenol acetate (5.62%), and β‐caryophyllene (1.39%).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, the three major compounds of CO were found to be eugenol (61%), β‐caryophyllene (17.9%), and eugenol acetate (11.73%) by GC‐MS (Table ). This is in accordance with previous results published by Prashar and others () and Tian and others (). According to Chaieb and others (), the major components of CO are eugenol (88.58%), eugenol acetate (5.62%), and β‐caryophyllene (1.39%).…”
Section: Resultssupporting
confidence: 94%
“…According to Chaieb and others (), the major components of CO are eugenol (88.58%), eugenol acetate (5.62%), and β‐caryophyllene (1.39%). In agreement with those measurements, Tian and others () reported that the major constituents of CO are eugenol (88.61%), eugenol acetate (8.89%), and β‐caryophyllene (1.89%). However, the exact chemical composition of CO was slightly different in different studies.…”
Section: Resultssupporting
confidence: 82%
“…Thymol is known to have contact toxicity against SWD with an LD 50 value of 1.73 µg/fly [ 11 ]. Although the contact toxicity of eugenol against SWD was not tested in this study, contact toxicity of eugenol against insect pests is well known [ 31 , 32 , 33 ]. Activity of thymol and eugenol may be attributed to the contact toxicity of allspice and clove bud, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing other reports, content of eugenol has been reported in values more or less similar to this value: e.g. 58.29% (22), 59.29% (23), 76.8% (24), 86.61% (25) and 88.58% (26).…”
Section: Discussionmentioning
confidence: 61%